Translation, adaptation and digital media - Milton, John, 1956-; Cobelo, Silvia, 1960- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Adaptation has always been central to Translation Studies, and, as print media becomes less and less dominant, and new media become central to communication, Adaptation is more than ever a vital area of Translation and Translation studies. This is the only user-friendly textbook covering the full area of translation and adaptation applicable to any language combination. Divided into nine chapters, it includes a wide range of texts from Brazilian culture, ensuring an ex-centric view of translation. Each chapter contains an expository section, case studies, and student activities to support learning. It emphasises the central role of Adaptation in the translation of works for the popular book market, and the theatre, cinema, radio, and specially, the new media. This is the essential textbook for students in Translation and Adaptation Studies courses and instructors and professionals working on adaptation projects"--
Keywords: Translating and interpreting; Adaptation (Literary, artistic, etc.); Digital media; LANGUAGE ARTS & DISCIPLINES / General; LANGUAGE ARTS & DISCIPLINES / Linguistics